Analysis of factors affecting mothers' behavior in selecting nutritious food for toddlers from the perspective of sharia financial literacy - Lidia Aditama Putri; Kholid Albar; Dewi Kartika Sari; Firdatul Ikhwati Istianah; Zunita Zunita (Science Midwifery, 2026)
The selection of nutritious foods for toddlers is one of the key factors in stunting prevention and is strongly influenced by mothers' ability to manage household resources. This study aimed to analyze the relationship between Sharia financial literacy and mothers' behavior in selecting nutritious foods, as well as to identify the factors that most strongly influence such behavior. This study employed an analytic quantitative design with a cross-sectional approach involving 108 mothers with toddlers in Gresik Regency. The sample was selected using purposive sampling, and data were collected through a Google Form-based questionnaire. Data analysis was conducted through univariate, bivariable, and multivariable analyses using Spearman's rank test and logistic regression. The results showed that the majority of respondents had moderate Sharia financial literacy (59.3%) and fair nutritious food selection behavior (50.9%). There was a significant relationship between Sharia financial literacy and nutritious food selection behavior (p < 0.05). In the multivariable analysis, access to nutritious food and Sharia financial literacy were shown to have significant effects, with access to nutritious food emerging as the most dominant factor. This study indicates that strengthening Sharia financial literacy and improving access to nutritious food are important in supporting mothers' behavior in selecting nutritious foods for toddlers.